2001
DOI: 10.1136/heart.86.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Long axis excursion in aortic stenosis

Abstract: Objectives-To examine long axis excursion in patients with all grades of aortic stenosis and preserved transverse systolic function, and to compare long axis excursion in symptomatic with that in asymptomatic severe aortic stenosis. Design-Prospective comparative study. Setting-Regional cardiothoracic centre. Patients-78 patients with all grades of aortic stenosis and normal fractional shortening and ejection fraction were studied. There were two comparison groups, 10 age matched normal subjects and 14 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 28 publications
2
27
1
1
Order By: Relevance
“…This myocardial impairment and structural changes initially and mainly involve the subendocardium [40], affecting longitudinal function, which is not well assessed by EF, but can be assessed by other indices that use M-mode and/or tissue Doppler imaging to analyze the lateral displacement of the mitral annulus [41].…”
Section: Discussionmentioning
confidence: 99%
“…This myocardial impairment and structural changes initially and mainly involve the subendocardium [40], affecting longitudinal function, which is not well assessed by EF, but can be assessed by other indices that use M-mode and/or tissue Doppler imaging to analyze the lateral displacement of the mitral annulus [41].…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous studies have shown longitudinal function to be an important marker of myocardial function in patients with severe AS and normal LVEF. [30][31][32] LV longitudinal shortening is more closely associated than ejection fraction with changes in symptom status, and may closely reflect alterations in subendocardial myocardial function. 31 Despite the absence of symptoms and a normal LVEF, patients with severe AS have an increased Zva.…”
mentioning
confidence: 99%
“…12, 16 Aurigemma et al compared hypertensive patients with LV hypertrophy and clinically normal patients, and demonstrated that high relative wall thickness allows for a normal EF despite depressed shortening at the midwall and along the long axis. 25 Takeda et al studied patients with AS and normal EF and found that the long axis excursion was lower in the AS population compared with normal individuals 26 ; moreover, short axis excursion was independently related to the grade of AS, being worse in patients with symptomatic disease. 26 In a recent study comparing the impact of myocardial fibrosis in patients with symptomatic severe AS, the longitudinal systolic function correlated with the degree of myocardial fibrosis and, moreover, predicted functional improvement after AVR.…”
Section: Ef In Plfas Patientsmentioning
confidence: 98%
“…25 Takeda et al studied patients with AS and normal EF and found that the long axis excursion was lower in the AS population compared with normal individuals 26 ; moreover, short axis excursion was independently related to the grade of AS, being worse in patients with symptomatic disease. 26 In a recent study comparing the impact of myocardial fibrosis in patients with symptomatic severe AS, the longitudinal systolic function correlated with the degree of myocardial fibrosis and, moreover, predicted functional improvement after AVR. 20 Interestingly, in this study, severe fibrosis was found in patients with normal EF, and EF was not predictive of better outcome after AVR.…”
Section: Ef In Plfas Patientsmentioning
confidence: 98%